Effect of sirolimus on malignancy and survival after kidney transplantation: systematic review and meta-analysis of individual patient data. (24th November 2014) - Knoll, Greg A; Kokolo, Madzouka B; Mallick, Ranjeeta; Beck, Andrew; Buenaventura, Chieny D; Ducharme, Robin; Barsoum, Rashad; Bernasconi, Corrado; Blydt-Hansen, Tom D; Ekberg, Henrik; Felipe, Claudia R; Firth, John; et al.
Abstract : Objective To examine risk of malignancy and death in patients with kidney transplant who receive the immunosuppressive drug sirolimus. Design Systematic review and meta-analysis of individual patient data. Data sources Medline, Embase, and the Cochrane Central Register of Controlled Trials from inception to March 2013. Eligibility Randomized controlled trials comparing immunosuppressive regimens with and without sirolimus in recipients of kidney or combined pancreatic and renal transplant for which the author was willing to provide individual patient level data. Two reviewers independently screened titles/abstracts and full text reports of potentially eligible trials to identify studies for inclusion. All eligible trials reported data on malignancy or survival. Results The search yielded 2365 unique citations. Patient level data were available from 5876 patients from 21 randomized trials. Sirolimus was associated with a 40% reduction in the risk of malignancy (adjusted hazard ratio 0.60, 95% confidence interval 0.39 to 0.93) and a 56% reduction in the risk of non-melanoma skin cancer (0.44, 0.30 to 0.63) compared with controls. The most pronounced effect was seen in patients who converted to sirolimus from an established immunosuppressive regimen, resulting in a reduction in risk of malignancy (0.34, 0.28 to 0.41), non-melanoma skin cancer (0.32, 0.24 to 0.42), and other cancers (0.52, 0.38 to 0.69). Sirolimus was associated with an increased risk of death (1.43, 1.21 to 1.71) compared with controls. Conclusions Sirolimus was associated with a reduction in the risk of malignancy and non-melanoma skin cancer in transplant recipients. The benefit was most pronounced in patients who converted from an established immunosuppressive regimen to sirolimus. Given the risk of mortality, however, the use of this drug does not seem warranted for most patients with kidney transplant. Further research is needed to determine if different populations, such as those at high risk of cancer, might benefit from sirolimus.